Evaluation of Adherence to Treatment Regimen in Patients with Type 2 Diabetes - Fazel Dehvan; Reza Ghanei Gheshlagh; Zhina Banafshi; Mahsa Moradiani (Hamadan University of Medical Sciences, 2023)
Background and Objective: Performing preventive activities with active participation of patients and adhering to treatment regimen are the most important behaviors relating to diabetes that ensure the health of the patients and reduce the severity of their complications. This study  aimed to evaluate the adherence to treatment regimen in patients with type 2 diabetes referred to Sanandaj diabetes clinic, 2018, Iran. Materials and Methods: In the present study, 181 patients with diabetes were referred to the Sanandaj Diabetes Clinic in Kurdistan, Iran. Following the inclusion criteria, they were selected using a convenience sampling method. Data was collected using a demographic checklist and a standard treatment adherence questionnaire in chronic patients. Data analysis was performed using SPSS software (version 16). The collected data was analyzed by descriptive (frequency, percentage, mean and standard deviation) and inferential tests. Results: The level of treatment adherence to the studied units was moderate. The mean overall score and score of different dimensions of treatment adherence in patients with abnormal glycosylated hemoglobin was significantly higher than in patients with normal glycosylated hemoglobin (P<0.001). In addition, the mean score of treatment adherence in the ability dimension was higher in insulin users than in pill users (P=0.042). In the  commitment dimension, pill users were more than insulin users (P=0.023). Conclusion: Considering the moderate level of treatment adherence, it seems necessary to provide solutions to improve the level of treatment adherence, especially in integrating treatment with life and enhancing the patients' desire to participate in treatments.